Strategi Impulsive Buying Shoppe Live: Pengaruh Influencer, E-WOM, dan Promosi Melalui Harga sebagai Variabel Intervening - Agus Priadi Agus Priadi; Slamet Heri Winarno; Aloysius Rangga Aditya Nalendra (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the effect of influencer, Electronic Word of Mouth (E-WOM), and promotion on impulse buying on Shopee Live, with price as an intervening variable. This research adopts a quantitative approach using Structural Equation Modeling (SEM) based on Partial Least Square (PLS). The population consists of Shopee users in the Greater Jakarta area (Jabodetabek), with a sample of 196 respondents determined using the Lemeshow method.The results indicate that influencer, E-WOM, promotion, and price have a positive and significant effect on impulse buying. Price is found to be the most dominant factor with a coefficient of 0.392, followed by promotion (0.267), E-WOM (0.241), and influencer (0.218). Furthermore, price significantly mediates the relationship between influencer, E-WOM, promotion, and impulse buying. The R-square value of 0.703 demonstrates that the model has strong explanatory power for impulse buying behavior.These findings suggest that impulse buying behavior on Shopee Live is not purely spontaneous but is influenced by emotional stimuli, social validation, and rational evaluation of price. Therefore, effective marketing strategies should integrate promotion, influencer marketing, and E-WOM with appropriate price management to enhance consumers’ impulse buying decisions.